(untitled) (KYAMC Journal, 2023)
Idiopathic Granulomatous Mastitis (IGM), or Granulomatous Lobular Mastitis (GLM) or simply GM (Granulomatous Mastitis) is a benign chronic and sometimes recurrent inflammatory process of unknown etiology, involving one or both breasts, commonly in women of childbearing age. In has no definite diagnostic hallmark or marker. It is to be diagnosed by exclusion of all other diseases. Biopsy is mandatory. A challenge is there to differentiate IGM from other diseases including malignancy, tuberculosis and other granulomatous reactions, It has no specific curative treatment. Breastfeeding from the IGM breast is safe, if not on immunosuppressive or steroid treatment. It has long been classically treated with oral steroids with or without such other immunomodulators as methotrexate, azathioprine etc. Recently, intralesional triamcinolone injection has been shown to improve the symptoms. But local high concentration intralesional triamcinolone, systemic immunosuppressive agents are unsafe for breastfed babies. If a woman chooses systemic treatment, after Shared Decision Making (SDM), she should be cautioned about milk suppression and untoward effects both in mother and baby. Some women prefer no medication during lactation. Complicated cases or failure of conservative treatment calls for surgical treatment in the form of local wide resection or mastectomy etc. The patients may suffer physically, mentally, and economically, significantly lowering the quality of life. There is no consensus on its management strategies. Its management still remains as a challenge. We like to review, discuss, and share about its masked etiology, presentations, diagnostic aids plus the available avant-garde optimum management strategies. KYAMC Journal Vol. 13, No. 04, January 2023: 250-256